PERANAN KEPEMIMPINAN DALAM ORGANISASI KEPOLISIAN - Aliffiah Novi Ramadhini; Muhammad Saefuddin, Jesyinda Putri Wibowo, Tugimin Supriyadi (CV. ADIBA AISHA AMIRA, 2024)
This journal was written with the aim of knowing the role of leadership in police organizations. Leadership is attitudes and behavior to influence subordinates so that they are able to work together, so that they can form harmonious cooperation. Leadership theory aims to explain how a leader's behavior influences the motivation and work performance of his subordinates, in different work situations. The ability to control resources and other factors to achieve organizational goals is an effort that must be carried out in every organization. In writing this journal, the process carried out by the author is to look for material references in the journal and other materials collected. The process of writing this journal involves working with materials, benefits, and concepts. Leaders in organizations need to communicate smoothly and effectively to achieve their goals by ensuring continuous improvement or quality improvement in organizational performance and human resource performance. Therefore, almost all members of an organization must understand the organizational communication process in order to correctly understand that there are no errors in communication between them.